RANCANG BANGUN SISTEM KENDALI UNIT PENGOLAHAN AIR BERSIH BERBASIS ARDUINO UNO R3 DAN NEXTION - Supriyadi, Achmad; Setyawan, Agus; Suseno, Jatmiko Endro (BERKALA FISIKA, 2019)
The control of the ordinary water treatment unit on refinery location is still operated manually(by operator), especially in the filtering unit (IRF unit). There are 9 manual block valves that must be operated every 8 hours, to keep the water quality meets its specification. Manual operation can increase the risk of errors or delays in the operation or movement of service cycles and regeneration sequences. Subsequently, it can decrease the water quality and unefficiency in production. The automation of the water treatment unit was made using the nextion HMI touch screen circuit, Arduino Uno microcontroller, IC shift register, electronic relay and other electronic components. By connection between the Nextion HMI as an interface and the Arduino Uno microcontroller as electronic relay controller, the design of the control unit was able to control the clean water treatment unit simulator in accordance with the principles of the processing unit.Keywords: Water treatment unit, nextion, arduino uno